Design of phase shifters in nanowire membrane technology and VCOs in CMOS technology at millimeter-waves for future full frontend integration. - Gomes, Leonardo Amorese Gallo (2022)
This doctoral thesis is inserted into the complex context of millimeter-wave telecommunications, dealing with two very important elements in a transceiver for such frequencies: phase shifters and voltage-controlled oscillators. The phase shifters designed in this work are based on the metallic nanowire membrane technology platform (MnM), using suspended, slow-wave lines and liquid crystal. The suspended lines have the main advantage of showing low transmission losses, thanks to the absence of losses of air, keeping the length reduction thanks to the slow-wave effect. The insertion of liquid crystal to the suspended lines intensifies the slow-wave effect and allows the phase velocity controls of the line. Also, it lowers the pull-in voltage of the line, allowing it to work as a MEMS phase-shifter. This electrostatic switching causes a significative decrease of phase velocity, resulting in compact and high-performance phase shifters. The values for the figure of merit are 43.8 °/dB for a pure liquid crystal phase shifter and 108 °/dB for a phase-shifter that combines the phase shift generated by the liquid crystal and MEMS switching. These results show the strong potential of this topology for millimeter wave applications. The voltage-controlled oscillators were designed in a RF-oriented BiCMOS technology, the 55-nm BiCMOS technology developed by ST Microelectronics. This technology offers high-performance devices and a low-loss back-end. The oscillators use a novel tank circuit based in quarter-wavelength stubs based in slow-wave coplanar striplines (S-CPS) periodically loaded by MOS varactors. The design started with the development of a resonator topology that maximizes varactor control over the phase velocity of the line, as well as a design procedure that enables the determination of the best possible resonator, given a set of design parameters. Also, some other elements of the oscillator were explored: first, the study of the tank loss compensation configuration; second, a bufferless topology, where the output power is derived directly from the tank circuit; third and last, the use of electronic switches to control a tunable transformer based on S-CPS. The oscillators were designed having a center frequency of 80 GHz and all have a frequency tuning range better than 10 %, while displaying a figure of merit better than -170 dB. One of the oscillators displayed a frequency tuning range of almost 20 %, covering the E-band completely and continually. These results show that the varactor-loaded S-CPS resonator is an innovative oscillator topology that is very powerful and flexible, enabling the design of compact and high-performance oscillator of millimeter-wave applications.